Silver(I) and zinc(II) complexes with symmetrical cinnamaldehyde Schiff base derivative: Spectroscopic, powder diffraction characterization, and antimycobacterial studies - Amaral, Thaeny C.; Miguel, Fábio B.; Couri, Mara R.C.; Corbi, Pedro P.; Carvalho, Marcos A.; Campos, Débora L. [UNESP]; Pavan, Fernando R. [UNESP]; Cuin, Alexandre (Elsevier, 2018)
Silver(I) and zinc(II) complexes with N,N′-bis(trans-cinnamaldehyde)ethane-1,2-diamine (EnCinn) have been synthesized and characterized by elemental analysis, simultaneous thermogravimetric and differential thermal studies (TG-DTA), infrared (IR), 1H and 13C nuclear magnetic resonance (NMR) spectroscopic measurements and electrospray ionization quadrupole time-of-flight mass spectrometry (ESI-QTOF-MS). Crystal and molecular structure descriptions were performed based on powder X-ray diffraction data. The AgEnCinn complex has a polymeric structure where the ligand bridges between two Ag(I) ions, while the ZnEnCinn complex has a monomeric structure with EnCinn acting as chelating ligand. Antimycobacterial assays over Mycobacterium tuberculosis showed the activity of the Ag(I) complex with Minimum Inhibitory Concentration (MIC) value of 22.7 μmol L−1, while the Zn(II) complex was shown to be inactive over the same experimental conditions.
Keywords: Cinnamaldehyde; Metal ions; Powder diffraction; Schiff bases; Tuberculosis